2005
DOI: 10.1002/tea.20053
|View full text |Cite
|
Sign up to set email alerts
|

Improving science inquiry with elementary students of diverse backgrounds

Abstract: This study examined the impact of an inquiry-based instructional intervention on (a) children's ability to conduct science inquiry overall and to use specific skills in inquiry, and (b) narrowing the gaps in children's ability among demographic subgroups of students. The intervention consisted of instructional units, teacher workshops, and classroom practices. The study involved 25 third-and fourthgrade students from six elementary schools representing diverse linguistic and cultural groups. Quantitative resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
137
1
18

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(167 citation statements)
references
References 26 publications
4
137
1
18
Order By: Relevance
“…In and of itself, this is not surprising. Much of the literature presented in the second chapter of this study suggests that demographic differences exist in science experiences (Brotman & Moore, 2008;Scantlebury & Baker, 2007;Lee & Buxton, 2008;Aikenhead, 2001;Cuevas et al, 2005). However, results from this study indicated that these variables accounted for the variance in the initial starting points of science achievement but the growth rates of each subgroup were not statistically different.…”
Section: Summary Of Findingscontrasting
confidence: 54%
See 2 more Smart Citations
“…In and of itself, this is not surprising. Much of the literature presented in the second chapter of this study suggests that demographic differences exist in science experiences (Brotman & Moore, 2008;Scantlebury & Baker, 2007;Lee & Buxton, 2008;Aikenhead, 2001;Cuevas et al, 2005). However, results from this study indicated that these variables accounted for the variance in the initial starting points of science achievement but the growth rates of each subgroup were not statistically different.…”
Section: Summary Of Findingscontrasting
confidence: 54%
“…Culturally responsive curricula appear to focus on inquiry, the integration of the English language with scientific literacy, as well as the incorporation of the primary language of these learners. Positive gains in science and literacy achievement have been reported (Fradd et al, 2002;Lee et al, 2008;Cuevas et al, 2005). Given that the achievement gap between different races and ethnic backgrounds may start earlier than expected (see Chapin, 2007), infusing science literacy into language instruction may be a potential solution to closing this achievement gap.…”
Section: Race Ethnicity and Socioeconomic Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Araştırmanın bulguları aynı zamanda; farklı etkinlikler, yöntemler ve araçlar ile öğrenme ortamlarının zenginleştirilerek araştırma becerilerinin geliştirilmesinin amaçlandığı çalışmalarla (Alkan-Dilbaz, 2013;Brickman, Gormally, Armstrong ve Hallar 2009;Chu vd., 2008;Cuevas, Lee, Hart ve Deaktor, 2005;Güneş, 2011;İlter, 2013;Wu ve Hsieh, 2006;Yıldırım, 2007) uyumludur. Wu ve Hsieh (2006), araştırma temelli öğrenme ortamlarının, Yıldırım (2007) İlter (2013) ise Sosyal Bilgiler dersinde 5E öğrenme döngüsü modelinin öğrencilerin araştırma becerilerini geliştirmede etkili olduğu sonucuna ulaşmışlardır.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…When general inquiry-based teaching model was used, it was too challenging to low achievement students. They cannot feel the excitement and fun from scientific inquiry and finding, therefore, it will lead to either low engagement or empty-handed return of low achievement student (Champagne & Klopfer, 1977;Cuevas, Lee, Hart, & Deaktor, 2005;Welch, Klopfer, Aikenhead, & Robinson, 1981). From the past related literature, it was found that teaching strategy of situated interesting and metacognitive scaffolding triggering low achievement student has positive action on enhancing their scientific learning (Hidi & Renninger, 2006;Ben-David & Zohar, 2009).…”
Section: Introductionmentioning
confidence: 99%